GOVERNANCE OF ELEMENTARY EDUCATION: AN ANALYTICAL VIEW - Aman, Rameesha; Saeed, Amir; Sami, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The issue of education, and making it accessible to the public, has been one of the major concerns of Pakistan since decades. It is a problem which has garnered quite a lot of attention over the years, both at home and abroad. Education at the elementary level requires special attention because this is the most critical stage of an individual’s entire academic trajectory, and has important implications for the country as well. The Punjab government has recently launched many new schemes in order to increase enrollment rates and to provide this basic facility to the vast millions deprived of it. The method chosen for this purpose has been public-private partnerships and privatization, with the help of millions of dollars in aid from international donor agencies. This paper argues that these projects initiated by the Punjab government are based on neo-liberal policies which challenge the spirit of public service and create further inconsistencies in the society. Specifically, the implementation of new managerialism in local governance has meant that the right for education for all is seriously undermined, and has further eroded the belief in the state as the provider of basic necessities. The paper then argues that these concerns require policy re-examinations and changes in order to reverse the damage incurred through these reforms.